Assessing land‐use/water‐quality relationships across contrasting geologic areas in New Jersey. (28th October 2022) - Procopio, Nicholas A.; Zampella, Robert A.
Abstract: In all, 13 stream water‐quality parameters, including specific conductance (SC), pH, dissolved oxygen (DO), dissolved organic carbon (DOC), three nutrients, and six major ions were compared between the northern bedrock and southern coastal plain regions of New Jersey, USA and related to watershed‐disturbance gradients characterized by the percentage of urban land, impervious surface (IS), agriculture, and altered land (sum of urban land and agriculture) in the watersheds. SC, DO, calcium, magnesium, sodium, and chloride concentrations were greater in the north. DOC was higher and pH was lower in the south. Nutrient, potassium, and sulfate concentrations did not differ between regions. Regional water‐quality differences are attributed to geologic setting and land use. Except for DO in southern streams, all water‐quality parameters were related to urban land, agriculture, or both. Significant correlations between urban land and IS and water‐quality variables were similar in both regions with differences in unitless correlation coefficients ranging from 0.00 to 0.06. Compared to urban land and agriculture, relationships between most water‐quality variables and altered land were stronger in the south. The extent of urban and agricultural lands in the watersheds did not differ by region. Altered land was correlated with urban land in both regions and with agriculture only in the south. Although focused on New Jersey, this study has broader implications for watershed planning.